1997
DOI: 10.1038/sj.bmt.1700295
|View full text |Cite
|
Sign up to set email alerts
|

A single, double lumen high-flow catheter for patients undergoing peripheral blood stem cell transplantation. Experience at the National Cancer Institute in Mexico

Abstract: Summary:fusion of PBSC and the i. -106). The incidence of infectiousWe present our experience at the Instituto Nacional de Cancerología in Mexico, with the installation and care of complications was 2.2 ؋ 1000 catheter-days (1.7 Permacath and 3.0 Mahurkar); during neutropenia it was an IVTT including apheresis collection, reinfusion of PBSC and intravenous and hematological support of patients 3.7 ؋ 1000 cathether-days. The incidence of thrombosis was 0.9 ؋ 1000 catheter-days. There was a total of seven under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Finally, for six large reports in which central venous catheters were used for 1-533 days during transplantation, bloodstream infections ranged from 4 to 39%. 42,[52][53][54][55][56] In our study and in the published literature, the majority of the organisms recovered were skin commensals. Recent studies have reported reduction of infection in patients undergoing conventional chemotherapy with non-tunneled antiseptic-impregnated or antibiotic-coated catheters.…”
Section: Dicussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Finally, for six large reports in which central venous catheters were used for 1-533 days during transplantation, bloodstream infections ranged from 4 to 39%. 42,[52][53][54][55][56] In our study and in the published literature, the majority of the organisms recovered were skin commensals. Recent studies have reported reduction of infection in patients undergoing conventional chemotherapy with non-tunneled antiseptic-impregnated or antibiotic-coated catheters.…”
Section: Dicussionmentioning
confidence: 53%
“…[36][37][38][39][40][41] PBPC collection requires the use of high-flow catheter for adequate cell collection through apheresis, and supportive care needs may be extensive. 42 To execute the subsequent transplant, in addition, requires a conventional central venous catheter. Hence, these requirements usually are achieved by insertion of two separate catheters.…”
Section: Dicussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 32 of 112 (29%) catheter dysfunction occurred, and in 7 of 112 (6.3%) catheters were removed because of infection or mechanical problems. Other authors report a similar complication rate in patients using a single double‐lumen catheter for apheresis and PBPC transplantation: 41 In 7.1 percent the catheter was removed because of thrombosis or infection, and in 32 percent dysfunction occurred. Both authors concluded that the use of one catheter for PBPC collection and transplantation should be considered because complication rates are similar to the rates reported in the literature using one central venous catheter line for the transplantation only.…”
Section: Infusion Of Autologous Bm and Pbpcsmentioning
confidence: 70%
“…To ensure a fast infusion rate, cryopreserved products preferably should be infused using central venous lines. New hybrid, double‐lumen, large‐bore, flexible, long‐term catheters can accommodate both PBSC apheresis collection and transplant . Although long‐term, flexible, multiple‐lumen, tunneled central catheters are preferred, very often, an existing short‐term, nontunneled catheter is used instead.…”
Section: Discussionmentioning
confidence: 99%